Communication Strategy of Inaya Putri Hotel Bali Rebranding Into MERUSAKA Nusa Dua Bali Towards Customer Purchase Intention (Journal of Business and Management, 2022)
Abstract. Hospitality Industry, Merusaka Nusa Dua Bali official website stated that, Merusaka, formerly known as INAYA Putri Bali, the hotel are officially transformed into this new concept that is birthed after extensive thought. Rebranding aims to create new values and perception by customers towards the brand, and rebranding can be said to be successful if customers have a good perception of quality. This research aims to determine the attributes that influence customer purchase intentions on Merusaka through brand equity. Therefore, to gain the best results, the researcher has determined several variables to support this research and will be analyzed using the (PLS-SEM) method. The results showed that almost all of the predetermined variables influence customer purchase intentions through brand equity. However, brand awareness found to not influence brand equity. In addition, the majority of respondents had awareness of Merusaka Nusa Dua Bali, it is not followed by a high number of customer purchase intentions. The brand must not only be concerned about the customer's awareness of the brand, but also has to pay attention to the customer's engagement with the brand.Keywords: Hospitality Industry, brand equity, purchase intention, rebranding, marketing communication strategy, brand awareness, brand image, perceived quality, PLS-SEM